2009
DOI: 10.1507/endocrj.k08e-208
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Mutation in Papillary Thyroid Carcinoma in a Japanese Population: Its Lack of Correlation with High-Risk Clinicopathological Features and Disease-Free Survival of Patients

Abstract: Abstract. Recent studies have demonstrated that BRAF V600E mutation is a common event in papillary thyroid carcinoma and a majority of these lesions have shown a direct relationship between BRAF V600E mutation and aggressive characteristics, including a worse patient prognosis. However, there are no studies from Japan regarding this issue in a large series with adequate postoperative follow-up periods. We investigated BRAF V600E mutation in 631 patients with papillary carcinoma having median follow-up periods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
203
8
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(239 citation statements)
references
References 44 publications
20
203
8
3
Order By: Relevance
“…The most prevalent subgroup of classical and follicular variants of PTC showed no association of BRAF mutation with poor prognostic factors or poor outcome. Our findings corroborated recent studies (20,21,22,23) and also discarded the association of p.V600E with higher frequency of cervical LN and distant metastases (13,24,25,26). In order to justify the lack of association, it has also been proposed that it is not the intratumoral presence of BRAF mutation that determines prognosis but the higher frequency of mutant BRAF alleles, identified in an innovatory analysis of pyrosequencing technique, that favors more frequent recurrence (27).…”
Section: Clinical Study D L S Danilovic and Others Preoperative Molecsupporting
confidence: 91%
“…The most prevalent subgroup of classical and follicular variants of PTC showed no association of BRAF mutation with poor prognostic factors or poor outcome. Our findings corroborated recent studies (20,21,22,23) and also discarded the association of p.V600E with higher frequency of cervical LN and distant metastases (13,24,25,26). In order to justify the lack of association, it has also been proposed that it is not the intratumoral presence of BRAF mutation that determines prognosis but the higher frequency of mutant BRAF alleles, identified in an innovatory analysis of pyrosequencing technique, that favors more frequent recurrence (27).…”
Section: Clinical Study D L S Danilovic and Others Preoperative Molecsupporting
confidence: 91%
“…The prognostic value of the BRAF V600E mutation in PTC patients has been an object of extensive studies. While many studies report an association of BRAF V600E mutation with a more aggressive behavior (13,16,17,20,22), others, including the present series, failed to document such association (14,18,19,21). These apparently conflicting results have to be reevaluated in light of a recent study (38) demonstrating that clonal occurrence of BRAF mutation is a rare event in PTC and that more frequently this mutation affects only a subpopulation of cells.…”
Section: Discussioncontrasting
confidence: 59%
“…The V600E mutation constitutively activates BRAF kinase, leading to prolonged stimulation of the MAPK pathway, which ultimately leads to uncontrolled cell proliferation and faulty apoptosis (8,9,12). The majority of studies have associated BRAF V600E mutation with a more aggressive PTC behavior, whereas a few studies failed to reproduce this finding (13,14,15,16,17,18,19,20,21,22). Still, its value as a prognostic marker remains incompletely established and other players might be implicated, justifying the search for additional molecular markers.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of any associations between BRAF mutation and advanced clinicopathologic features 28 reported that high iodine intake is a significant risk factor for BRAF mutation, and a meta-analysis showed that a high prevalence of the BRAF V600E mutation tended to have a smaller meta-risk of extrathyroidal invasion and lymph node metastasis 7 . Second, a significant number of our patients underwent subtotal thyroidectomy or lobectomy, which might lead to an underestimation of aggressive pathologic characteristics 21,29 . Consistent with an earlier study 7 , BRAF mutation was confirmed as an independent predictor of recurrence in our cohort at 3 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to BRAF mutation, RET/PTC rearrangement has been associated with better prognosis 15 . Yet despite those findings, controversy remains [16][17][18][19][20][21] . In addition, questions about the clinical significance of these mutations in the management of microptc are ongoing 22 .…”
Section: Introductionmentioning
confidence: 99%